ANALISIS STRUKTUR, PERILAKU DAN PENAMPILAN PASAR KELAPA DI KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR (STUDI KASUS DESA SARI MULYA DAN DESA PENJURU) - Samsul Aripin; Jum’atri Yusri; Novia Dewi (Fakultas Pertanian, Universitas Riau, 2021)
This research aims to analyze the structure, conduct and performance of the coconut market in the villages of Sari Mulya and Penjuru Kateman Subdistcrict. Sampling of farmers using accidential sampling and merchant sample using census method. Data analysis with descriptively and quantitatively. Descriptively the market structure is seen through the number of market participants and barriers in and out of the market, market behavior seen through the practice of price formation, correlation and price transmission. Quantitatively, market structure analysis uses concentration ratio, market share and herfhindhal index, analysis of market behavior using correlation analysis and price transmition while market appearance seen from marketing margin. The results of this research are (1) coconut marketing channel in Sari Mulya Village and Penjuru Village consist of four channel, the first channel is from farmer directly to the final consumer, the second channel from farmer to collecting merchant and final consumer, the third marketing channel is from farmer to collecting merchants, wholesalers and the final consumers and the fourth marketing channels from farmers to wholesalers, wholesalers and exporters (2) the market structure has a larger number of sellers than the buyer, has barriers in and out of the market and in the form of an oligopsony market, (3) Market behavior indicates that factories and traders dominate the market, this is seen from the value of the transmission price <1; (4) Market appearance shows that marketing channel II and marketing channel III are the channels with the lowest margin among the four channels in Sari Mulya and Penjuru Villages.